Improved the Durability of Thermal Barrier Coatings with Interface Modified by Three‐Dimensional Mesh Patterns. Issue 10 (21st June 2016) - Luo, L.; Zhang, X.; Zou, Z.; Guo, F.; Qi, H.; Zhao, X.; Xiao, P.
Abstract : An approach to improve the lifetime of air plasma sprayed (APS) thermal barrier coatings (TBCs) by modifying the interfacial microstructure has been reported. The laser powder deposition technique was employed to fabricate the mesh structure (with the same composition as the bond coat) at the ceramic–substrate interface. After thermal cycling test, the APS TBCs with the mesh exhibited a much less spallation degree (5%–10%) compared with the reference samples without mesh (>50%), implying that the mesh is effective in impeding the crack propagation along the interface. In addition, the effect of the mesh geometry parameters, e.g., height and spacing of mesh, on the spallation degree of TBCs was also investigated. Based on the results of experiment and calculation, the optimal mesh parameters were proposed.